If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)=(x2+4x-8)
We move all terms to the left:
(x-2)-((x2+4x-8))=0
We add all the numbers together, and all the variables
-((+x^2+4x-8))+(x-2)=0
We get rid of parentheses
-((+x^2+4x-8))+x-2=0
We calculate terms in parentheses: -((+x^2+4x-8)), so:We add all the numbers together, and all the variables
(+x^2+4x-8)
We get rid of parentheses
x^2+4x-8
Back to the equation:
-(x^2+4x-8)
x-(x^2+4x-8)-2=0
We get rid of parentheses
-x^2+x-4x+8-2=0
We add all the numbers together, and all the variables
-1x^2-3x+6=0
a = -1; b = -3; c = +6;
Δ = b2-4ac
Δ = -32-4·(-1)·6
Δ = 33
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-\sqrt{33}}{2*-1}=\frac{3-\sqrt{33}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+\sqrt{33}}{2*-1}=\frac{3+\sqrt{33}}{-2} $
| 3+52x=1-28x | | 17-x=1/3(15)=6 | | (3x-1)+(x+5)-5x=-(3x+9) | | 3/1+a=3/5 | | 8w-22=6w-14 | | -2z+6=2 | | N+2n=51 | | 10x-168=2x+48 | | 10x-9=7x+8 | | 0=4(3x^2-26x+42) | | 12v+13=v+24 | | 5x-3x+9-15x=123 | | (^3√25)=(1/125)^-x+3 | | 6y+-2=10 | | 2/3x-1/6=x+3/6 | | 15x-13+3x-5=180 | | 4x2+29x-24=0 | | 8v-6=v+22 | | 7x9+4x+22=90 | | 4x+4+5x=-41 | | 8/7=x/5 | | (x5+9x3–3x2+14x–21)/(x2+7)=x | | 17/7=9/u | | 33=19w | | 30=5(b=4) | | .70xN=222,100 | | 3x+11+8x+2=90 | | 2c-25=c-5 | | k1/5=3 | | 16x-18=6x+32 | | -25v-40=23-8v | | .70xX=222,100 |